THE ISSUE OF FORMING RATIONAL ECONOMIC POLICY OF ENVIRONMENTAL PROTECTION (Globalization and Business, 2023)
In the state the environmental policy faces three main issues, they are: The issue of internalization of external costs (i.e. the issue of transaction costs), informing issues and the issues of control.  The issue of transaction costs must be overcome by effective and active environmental policy. This can only be done if the ways of efforts of environmental policies are used to create (the use of instruments) situations on the market that are not voluntarily established. There is a precondition for this fact if the environmental policy conductors have enough information about relationship between natural resources,  production, technology  and  environmental impacts. In other ways how can we identify and deter- mine the quantity of harmful substances that are allocated by different pollutants (e.g. setting limits of environmental pollution). So far, there is a huge deficit of the possibilities of obtaining and reacting to the information by the National Environmental Protection Service Officials all over the world. It is also unclear whether the state has the possibility to examine the legality of the environmental law by the economic subjects (control problem), the discussion on the size of radioactive irradiation is still relevant. In case of violation of legislative norms on environmental pollution by the economic subjects, the controlling system must have more effective sanctions (violators should pay higher cost of expenses than expected benefits).An effective implementation of the goals of environmental policy is only possible by combined usage of legal and market economic instruments. The natural environmental resources are characterized by the attractiveness of the social product, thus we can deal with the environmental problems by existing the decentralized market in the economy, for this purpose of environmental policy, it is necessary that the state fulfill its functions of regulation.The formation of environmental policies in Georgia also takes place in many international obligations. In order to be closer to the developed international community, Georgia tries to implement internationally recognized environmental approaches and regulations where it is possible. The EU and Georgia have signed an Association Agreement, and one of the main issues is the scope of environmental protection. The Agreement provides a wide range of measures in environmental issues, which will facilitate environmental conditions not only for human beings and ecosystems but also would improve environmental management and effective decision-making procedures.The process of converting the national legislation of environmental protection to EU legislation implies several interconnected stages, namely:Analysis of EU environmental legislation to identify basic principles;Analysis of national legislation to assess compliance with EU principles;To  conduct  basic  principles  of  the  European Union in national legislation;Implementation of relevant institutional changes.